Tafsir Fikih-Sufistik al-Bahr al-Madid: Studi Penafsiran Ibnu Ajibah atas Ayat-ayat Fiqhiyyah - Hasan, Ilham Ali; Mubarok, Muhammad Hasani (LPPM IIQ An Nur Yogyakarta, 2022)
The tendency of mainstream interpretation in interpreting fiqh verses often only displays the outward meaning. This can lead to the reading of formalistic fiqh in interpreting the Koran. One of the interpretations that can display the zahir and inner meanings of the verse in a balanced way is the interpretation of al-Bahr al-Madid by Ibn Ajibah. This pattern of interpretation can be categorized as fiqh-sufistic. This research answers two questions; 1) how is the construction of the interpretation of fiqh-sufistic interpretation in QS al-Taubah (9):103 practiced by Ibn Ajibah? what are the implications of Ibn Ajibah's interpretation of QS al-Taubah (9):103? This research concludes; that the interpretation of Ibn Ajibah's al-Bahr al-Madid, when interpreting QS al-Taubah (9):103 displays a Sufistic-fiqh pattern, where a fiqh verse is not only seen as the main purpose of a verse, but is also seen from the spiritual side hidden behind the verse. This study also concludes that the implications of Ibn Ajibah's interpretation of QS al-Taubah (9):103 appear in two sides: 1) methodical implications; where the interpretation of al-Bahr al-Madid is able to present two tendencies of the outer and inner meaning of a verse by not mixing up the analysis. 2) practical implications; In this case, Ibn Ajibah, in interpreting the isyari side of the verse, conveys his views on the importance of being obedient to the teacher who is one's spiritual guide.